From the neurobiological basis of comorbid alcohol dependence and depression to psychological treatment strategies: study protocol of a randomized controlled trial - Becker, Alena; Ehret, Anna Magdalena; Kirsch, Peter (BMC psychiatry, 2017)
Alcohol use disorder and depression occur commonly in the community. Even though this high-prevalence comorbidity is associated with poorer posttreatment outcomes and greater utilization of costly treatment services, existing treatment trials often exclude patients with comorbid depressive and alcohol use disorders. Past research suggests that symptoms such as craving and anhedonia might be associated with alterations within the reward circuit, while emotion regulation deficits are related to disruptions within the default mode network. The aim of this clinical neuroimaging study is to transfer previous research about the reward circuit and default mode network underlying alcohol use disorder and depression to achieve a better understanding of neural signatures characterizing their comorbidity. In addition, the neurobiological results will be used to test whether two psychotherapeutic intervention programs, mindfulness-based training and behavioral activation training, are able to positively influence the identified pathomechanisms.
Gesehen am 26.09.2017